Measuring the service quality factors of perspective international students to improve their satisfaction and loyalty towards University Tun Hussein Onn Malaysia (UTHM) - Mohammed Alerqi, Eman Saleh Ahmed (2020)
Student satisfaction and quality of education are of compelling interest to students, academic staff, policymakers and higher education researchers internationally. Students’ expectations can influence levels of student satisfaction before their study and their pre-conceived beliefs regarding the value of their education. It concerns that with less emphasis on the quality of services that provided by the Higher Education Institution (HEI) to the students may pose a threat regarding the satisfaction, retention and recruitment of the students which reduces the competitiveness of the institution. This study seeks to measure the service quality success factors through the perspective of international students to improve their satisfaction and loyalty towards University Tun Hussein Onn Malaysia. A questionnaire survey was carried out among international students in UTHM. A total of 246 questionnaires were collected and found valid. Analysis of Moment Structures Equation Modelling (AMOS-SEM) model was developed and found that seven groups of factors for service quality influences the satisfaction and loyalty towards UTHM, these factors are namely teaching, course content and supervision; administrative services; academic facilities; campus infrastructure; support services; student’s satisfaction and student’s loyalty. The findings from the critical factors of service quality through path analysis using structural model indicated that administrative services; academic facilities and support services have a significant effect on student's satisfaction, and student's satisfaction has a significant impact on student's loyalty while teaching, course content and supervision; and campus infrastructure groups were not supported. The implication of this research could enhance and further strengthen UTHM structures and creating new output as an adaptable strategy and education management tool.